Investment promotion in Egypt: Institutional analysis of the general authority for investment and free zones - Ali, Rawda Said (AUC Knowledge Fountain, 2016)
The objective of this research is to critically examine the potential of Egypt’s central Investment Promotion Agency (IPA) to attract Foreign Direct Investment (FDI) and therefore contribute in boosting the country’s economic development. In quest of achieving this objective, the research applies a qualitative methodological approach of a single case study analysis, where it investigates several legislative and institutional elements to understand the extent to which the structure of the General Authority for Investment and Free Zones (GAFI) enables it to perform its role as the national agency responsible for investment promotion. The analysis explains various aspects that define the effectiveness of GAFI’s structure, such as the authority level, tools, degree of political autonomy, and the different promotional functions performed. The detailed scrutiny of different organizational and functional elements reveals that the overall structure of GAFI does not contribute to its likelihood of being an effective agency, and therefore exposes its limited role in promoting and facilitating private investments. The findings explain how GAFI’s legal status accounts for weakening its structure and further articulate how the Authority lags behind in performing the main promotional functions of image building, investment generation, investor servicing and facilitation, and policy advocacy; all of which that influence Egypt’s ability to attract foreign investment, enhance local economy and guarantee better linkages to global economy. Thus, the research offers some recommendations to help policy makers adopt better mechanisms that could enhance the performance of GAFI, such as, ensuring the separation between GAFI’s role as a regulator and executor on one side, and its role as promoter and facilitator on the other side.